The Joy of Modernization by Explaining the Fundamentals of Hadith Science (Muttalib Etiquette of Hadith or Hadith) by Sheikh Muhammad bin Mustafa Al-Shahawi (d. 1167 AH) - Mahmoud Zahir Hassan, (Islamic Sciences Journal, 2024)
ABSTRACT Let it be known that whoever is the first to hear the hadith must be sincere to God and correct in his intention, and it is desirable for him to perform ablution and perfume and to narrate the hadith to everyone who asks him, and it is desirable for him not to narrate it until he reaches the age of fifty, and if it happens before that, there is no problem because that has been proven from the imams, and someone who has reached eighty should not Fear of aging and change occurs, and it is desirable to open the dictation session by reading something from the Holy Qur’an, and to pray for the Prophet (may God bless him and grant him peace) and be pleased with the Companions (may God be pleased with them), and to have mercy on the Imams, and to pray for forgiveness for his sheikh, and not to limit himself to one sheikh, and the narrator is from the people of Knowledge of hadith, its causes, and its various aspects, along with being diligent and diligent in doing so, and acting according to what he has taught and learned.